2018
DOI: 10.1101/264093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lower performance of Toxoplasma-infected, Rh-negative subjects in the weight holding and hand-grip tests

Abstract: Toxoplasma, a protozoan parasite of cats, infects many species of intermediate and paratenic hosts, including about one-third of humans worldwide. After a short phase of acute infection, the tissue cysts containing slowly dividing bradyzoites are formed in various organs and toxoplasmosis proceeds spontaneously in its latent form. In immunocompetent subjects, latent toxoplasmosis was considered asymptomatic. However, dozens of studies performed on animals and humans in the past twenty years have shown that it … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…(2008) showed that in a Toxoplasma ‐free people, RhD‐positive homozygotes performed slightly worse on psychomotor tasks than RhD‐positive heterozygotes but much worse than RhD‐negative homozygotes. In Toxoplasma ‐infected subjects, on the other hand, RhD‐positive homozygotes performed equally poorly as RhD‐negative homozygotes, and much worse than RhD‐positive heterozygotes (see also Flegr et al., 2018, for a confirmatory study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008) showed that in a Toxoplasma ‐free people, RhD‐positive homozygotes performed slightly worse on psychomotor tasks than RhD‐positive heterozygotes but much worse than RhD‐negative homozygotes. In Toxoplasma ‐infected subjects, on the other hand, RhD‐positive homozygotes performed equally poorly as RhD‐negative homozygotes, and much worse than RhD‐positive heterozygotes (see also Flegr et al., 2018, for a confirmatory study).…”
Section: Discussionmentioning
confidence: 99%
“…Several papers showed that subjects with the RhD‐positive phenotype—and especially heterozygotes with one D and one d allele—are protected against certain adverse factors. Most prominent is protection against the health impact of toxoplasmosis, a common chronic infection by a protist parasite, but various studies also found indications of protection against the effects of fatigue, smoking and ageing (Flegr et al., 2010, 2012, 2018; Holub et al., 2011; Kaňková et al., 2010; Novotná et al., 2008). More recently, an ecological correlative study performed in 66 countries for which allele frequencies and WHO data on the incidence of 125 disorders were available (WHO, 2008) showed that the incidence of many disorders correlates positively with the frequency of RhD‐negative subjects and negatively with the frequency of RhD‐positive heterozygotes in the population (Flegr, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It will be therefore necessary to repeat the study on the population of people with empirically examined Rh phenotype, or preferably genotype. Such studies have been already done for other traits demonstrating, for example, the association between Rh phenotype and performance in weight-holding and handgrip tests [ 14 ], intelligence [ 13 ], psychomotor performance [ 10 12 ], and several personality traits [ 32 ]. It must be mentioned, however, that a large binational cohort study found no difference in mortality of Rh-positive and Rh-negative subjects [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of this immunological effect and sporadic reports about the possible association of Rh negativity with certain personality traits [ 9 ], no effects of the Rh genotype on human phenotype have been described. Recently, however, several studies suggested the existence of specific effects of Rh phenotype and genotype on human psychomotor performance [ 10 14 ] and health [ 15 17 ]. Generally, Rh-negative subjects have worse health, score worse in some performance tests, and express higher sensitivity to various negative environmental factors, such as Toxoplasma infection and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study might also point to such conclusions (Rh negative A blood type is most prevalent in subjects in a very severe stage of COPD), but this should be investigated in more detail. The Rhnegative phenotype was associated with a slower response to Toxoplasma gondii infection in the study of soldiers in the Czech Republic (FLEGR et al, 2009;FLEGR et al, 2018). A study conducted in Spain (Basque Country) highlighted the negative correlation between Rh-negative factor and liver transplantation (HANVESAKUL et al, 2008).…”
Section: Resultsmentioning
confidence: 99%